JARGON WARTAWAN: Leksikon Khas Cermin Kehidupan Profesi Jurnalis - , Novita Purnaningsih ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purposes of this research are: (1) to describe the forms of linguistic units of journalistsâ jargon lexicons, (2) to explain the meanings and functions of the uses of the journalistsâ jargon lexicons, and (3) to describe the life of journalists through typical lexicons they use in their daily activities. This research was a qualitative descriptive which described the data as they were. The data were collected through interviews and the data sources were the verbal utterances of some journalists which were transcribed into written forms, which were commonly used by journalists through various features of conversation and mobile phoneâs short message service. Additional data were collected from the researcherâs personal experience as a journalist. In analyzing the data, contextual method was used to describe the contexts that affected the use of language. This method rely on contexts as an elemen that affect the pattern of language use in communication. Then, the presentation of the data was done by formal and informal methods. The results of data analysis show: (1) There are several forms of journalistsâ jargon lexicon units that can be classified according to word classes, i.e. nouns, verbs, and adjectives. Polymorfemic lexicons which are the result of morphological processes, such as affixation, compound, reduplication, abbreviation, and naturalization, are also found. In addition, there are also some lexicons which are derived from Javanese, English, and Arabic words, (2) Most common lexicons have different or new meaning when used within the scope of the journalist community, but there is also common lexicons that have the same meaning when used by journalists. In terms of meaning, there are some lexicons which have similar shape or physical condition